(untitled) (Revista Argentina de Cirugía, 2021)
Background: several strategies have been described for the treatment of complex abdominal wall defects. The component separation technique with transversus abdominis muscle release (TAR) allows adequate fasciomiocutaneos flaps mobilization to close the middle line and has low morbidity. Objective: to evaluate outcomes of TAR technique for the treatment of large incisional hernias. Material and methods: in the period between March 2013 and April 2017, all consecutive patients with TAR procedures with a minimum follow-up of 6 months were included. Demographics, operative and postoperative variables were analyzed. Results were expressed in medians. Results: a total of 14 TAR procedures were performed. Ten patients were men. The age was 60 (35-81) years and BMI was 28,2 kg/m². Seventy percent of the patients had at least two previous surgeries. CT scan was performed before surgery in all patients. Tanaka index was 24,5%. Seven patients had ASA < III. The defect size was 480 (224-720) cm² and mesh size 900 (500 - 1050) cm². Operative time was 248 (180 -341) minutes and hospital stay 3 (2-4) days. Two patients had surgical site infection. Postoperative follow-up was 20 (6-44) months. There was no recurrences. Conclusion: TAR technique is safe and reliable for the repair of large abdominal wall defects with low morbidity and recurrence rates. Therefore it should be taken into account in the surgical armamentarium.